Los recursos didácticos para desarrollar la práctica de normas de convivencia en los niños del Quinto Año de Educación General Básica de la Unidad Educativa “Tomás Oleas” cantón Colta, durante el período 2022-2023. - Estrella Llangari, Byron Stiven (2024)
The objective of this research was to analyze the didactic resources to develop the practice of coexistence norms in children of fifth grade of General Basic Education of the Educational Unit "Tomás Oleas", Colta Canton, school year 2022-2023. The methodology developed adopted a mixed and non-experimental approach, characterized by a descriptive and diagnostic framework, and included both bibliographic and field analysis, detailed in the corresponding section. To carry out the research, the observation technique was used and an observation form with 10 items was designed, applied to a specific group of 20 fifth grade students of the "Tomás Oleas" Educational Unit, because it was selected according to the researcher's criteria. In addition, the interview was used as a technique and as an instrument the interview guide directed to teachers, which contains 6 items and was applied to the fifth-grade teachers of the same educational unit. The results show that, when using didactic resources, students show interest, identify the type of resource, understand better, develop correctly and their communication is feasible with their teacher; On the other hand, regarding the second variable coexistence norms, the results showed that students resolve conflicts peacefully, obey their teacher, relate correctly with others, put into practice values and rules of coexistence usually; therefore, the implementation of a guide of didactic resources for the practice of coexistence norms in basic general education is suggested.